Assessing Millets and Sorghum Consumption Behavior in Urban India: A Large-Scale Survey - Kane-Potaka, Joanna; Anitha, Seetha; Tsusaka, Takuji W.; Botha, Rosemary; Budumuru, Muralidhar; Upadhyay, Shweta; Kumar, Parkavi; Mallesh, Karuna; Hunasgi, Raghavendra; Jalagam, Ashok Kumar; Nedumaran, Swamikannu (Frontiers in Sustainable Food Systems, 2021)
There is growing Aattention is growing by governments and industry in regard to the role played by millets can play to help build resilience for farmers and cope with climate change, resilience for farmers, malnutrition, diabetes and some other major issues. To understand public knowledge and practices of consuming millets (including sorghum) in urban areasAs a result, a survey was conducted with 15,522 individuals from seven major cities of India, to understand individuals’ knowledge and practice of consuming millets (including sorghum) using a structured questionnaire and the data were analyzed using descriptive and inferential statistics. It was found that Tthe largest group amongof early adopters of millets werehave been people with health problems (28%), it being the single largest reason for consuming millets, followed by those wanting to lose weight (15%) and those selecting millets for its taste (14%). There was a significant gap between people who were health conscious (91%) and those who were sure millets were healthy (40%). The major reason the respondents did not eat more millets was that it is was not eaten at home (40%), followed by reactions such as not liking the taste (22%). Reaching the urban consumers through social media is recommended, given that it is their main source of information. There was no statistically significant relationship between state-wise per capita production and frequency of consumption of millets in the urban areas (p = 0.236). In conclusion, it is important to focus on three keymajor actionsareas are recommended to enhance the consumption of millets; developing delicious products development to satisfy the taste, providing knowledge on nutritional and health facts on millets, and improvinge accessibility of millets in urban markets.